Evaluation of risk factors for severe pneumonia in children: the Pneumonia Etiology Research for Child Health study. - Wonodi, C; Deloria-Knoll, M; Feikin, DR; DeLuca, A; Driscoll, A; Moïsi, J; Johnson, H; Murdoch, DR; O'Brien, K; Levine, O; Scott, J (2012)
As a case-control study of etiology, the Pneumonia Etiology Research for Child Health (PERCH) project also provides an opportunity to assess the risk factors for severe pneumonia in hospitalized children at 7 sites. We identified relevant risk factors by literature review and iterative expert consultation. Decisions for inclusion in PERCH were based on comparability to published data, analytic plans, data collection costs and logistic feasibility, including interviewer time and subject fatigue. We aimed to standardize questions at all sites, but significant variation in the economic, cultural, and geographic characteristics of sites made it difficult to obtain this objective. Despite these challenges, the depth of the evaluation of multiple risk factors across the breadth of the PERCH sites should furnish new and valuable information about the major risk factors for childhood severe and very severe pneumonia, including risk factors for pneumonia caused by specific etiologies, in developing countries.